Experimental investigation on the vibration induced by slug flow in horizontal pipe - Al-Hashimy, Z.I. (Asian Research Publishing Network, 2016)
Pipes used for transporting produced oil are often experienced two-phase flows. In particular, the presence of slug flow pattern will cause generation of transient pressure force and shear exerted on the interior wall of the pipe. This can cause vibration induced problems. This paper presents experimental results that enhance the understanding of the mechanism of fluid structure interaction FSI phenomena, and the nature of resulted vibration due to slug flows. Vibration measurements were taken under various slug flow rates. The effects of water superficial velocities on the vibration characteristics were investigated. The results showed that the pipe displacements of the vibration increased gradually with increased water superficial velocities, at a fixed air superficial velocity, while the predominant frequencies decreased progressively when the water superficial velocities was increased. In addition, the average maximum displacements increased by 64 when the water superficial velocity increased from 0.65 m/s to 1.0 m/s. Meanwhile, a decrease of 9 in the averages of the frequencies was noticed when the water superficial velocity increased from 0.65 m/s to 1.0 m/s. An investigation of the induced vibration behavior to change in air superficial velocities is recommended. Â©2006-2016 Asian Research Publishing Network (ARPN).